Student Violence Directed Against Teachers: Victimized Teachers’ Reports to School Officials and Satisfaction With School Responses - Moon, Byongook (Journal of interpersonal violence, 2021)
Research indicates that violence against teachers has detrimental negative effects on teachers’ emotional and physical well-being, connectedness to school, job performance, and retention. However, no quantitative empirical research has been conducted to examine the extent of teacher victimization reported to school officials, school interventions to address teacher victimization, and teachers’ satisfaction with school handling of victimization. To address the limitations of prior research on teacher victimization, for a sample of 1,628 teachers in a large urban county, the present research investigates the extent of teacher victimization reported to school officials and examines school responses to teacher victimization. Furthermore, two key variables (school interventions and apologies from offending students) are tested as predictors of victimized teachers’ satisfaction with administrators’ responses to incidents. The findings indicate that the extent of reporting victimization to school officials by victimized teachers is quite high; however, a large number of victimized teachers perceived school intervention following incidents as ineffective and inadequate. Ordinal logistic regression analyses indicate that victimized teachers who report to school officials expect offending students to be disciplined and held accountable, and when this does not occur, they are dissatisfied. Overall, the findings suggest the urgent need for school administrators to review their current disciplinary policies regarding teacher-directed violence and to establish effective protocols to prevent and properly respond to teacher victimization.